2017
DOI: 10.1016/j.neuron.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Transmission Optimization Predicts Expression Loci of Long-Term Plasticity

Abstract: SummaryLong-term modifications of neuronal connections are critical for reliable memory storage in the brain. However, their locus of expression—pre- or postsynaptic—is highly variable. Here we introduce a theoretical framework in which long-term plasticity performs an optimization of the postsynaptic response statistics toward a given mean with minimal variance. Consequently, the state of the synapse at the time of plasticity induction determines the ratio of pre- and postsynaptic modifications. Our theory ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 89 publications
2
58
0
Order By: Relevance
“…We assumed that pre-and postsynaptic changes would match each other over time and ignored the dynamics of this process. This choice was motivated in part by the lack of experimental constraints and in part by the results of recent theoretical studies (Costa et al, 2017). We obtained only moderated levels of LTD compared to in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assumed that pre-and postsynaptic changes would match each other over time and ignored the dynamics of this process. This choice was motivated in part by the lack of experimental constraints and in part by the results of recent theoretical studies (Costa et al, 2017). We obtained only moderated levels of LTD compared to in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies found also a prominent postsynaptic component (Sjöström et al, 2007), mostly based on alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptor (AM-PAR) plasticity, as commonly observed in the hippocampus. Some recent studies (Costa et al, 2017) have investigated the theoretical implications of bi-lateral plasticity and concluded that synapses strive for extreme states (highconductance high-release probability, low-conductance lowrelease probability). LTP/LTD are by definition persistent changes, at least in the order of minutes to hours, but presumably longer.…”
Section: Methodsmentioning
confidence: 99%
“…section 4), data itself may guide the choice of metric. Surprisingly, the available and appropriately normalized experimental data is consistent with the Euclidean metric in P rel − q space [19], but there is probably not sufficient data to discard a metric based on metabolic cost. Gradient descent has been popular as an approach to postulate synaptic plasticity rules [7][8][9][11][12][13][14][15][16][17].…”
Section: Gradient Descent In Neurosciencementioning
confidence: 98%
“…In some cases, cost as performance of a biological system is measured in comparison to the absolute physical minimum [5] or an information theoretic optimum [1][2][3] without addressing the question of how a solution at or close to the minimum can be found. In other cases, cost is used to derive algorithms that move the system closer to the minimum [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In the second case, predictions entail update rules of neuronal quantities or differential equations for the time evolution of synaptic weights.…”
Section: Introductionmentioning
confidence: 99%
“…Previous modeling approaches of STP have used a system of 84 nonlinear ordinary differential equations to capture µ(t) separated in a number of 85 dynamic factors [4,11,23,24]. Our main result is that we propose a linear-nonlinear 86 approach inspired from the engineering of systems identification [33,[40][41][42][43][44][45][46][47] and the 87 Spike Response Model (SRM) for cellular dynamics [34,48,49]. Here, the efficacies are 88 modeled as a nonlinear readout, f , of a linear filtering operation:…”
mentioning
confidence: 99%